Himālaya darśana : Bābā Kālī Kamalīvālā śatavārshikī grantha - Sharma, Benishankar; Upadhyaya, Ramprit, 1936-; Bābā Kālī Kamalīvālā, fl. 1831-1896 (Bābā Kālī Kamalīvālā Pañcāyata Kshetra, 1980)
Centennial volume on Bābā Kālī Kamalīvālā Pañcāyata Kshetra, socioreligious institution founded by Bābā Kālī Kamalīvālā, fl. 1831-1896, Hindu religious leader; comprises articles on him and on the Himalayas.